Asthma and periodontal health in children - Davidović Bojana; Ivanović Mirjana; Bokonjić Dejan; Janković Svjetlana; Erić Jelena; Lečić Jelena (Vojnosanitetski Pregled)
Background/Aim. Oral health is an important part of overall health. Good oral health is important for oral diseases prevention and health maintenance of respiratory system. The aim of the study was to evaluate oral hygiene and periodontal health parameters of asthmatic children and to compare them with children without asthma as well as to evaluate those parameters according to type of used medications and time of taking medications in children with asthma. Methods. This epidemiological study included 68 children with asthma and 68 children without asthma or any other chronic disease aged from 6 to 16 years. Parameters used in this study were Greene-Vermillion index, Löe-Silness gingival index and Community Periodontal Index (CPI). Results. Good oral hygiene (31.1%) was more present in children without asthma whereas poor hygiene (20.0%) was more frequent in children with asthma (p < 0.001). Healthy gingiva was more frequent in children without asthma (25%) while mild (58.8%) and moderate gingival inflammation (5.9%) were more frequent in the group of children with asthma (p < 0.01). Mean CPI values were higher in children with asthma (p < 0.001). Mean values of Plaque Index, Gingival Index and CPI did not show statistically significant difference in relation to type of administered medication. However, taking medications in the afternoon was related to higher mean values of Plaque Index and Gingival Index (p < 0.05) within the group of children with asthma. Conclusion. Children with asthma had poorer oral hygiene and were diagnosed with greater values of oral hygiene and periodontal indices compared with the group of children without asthma. For this reason, it is necessary to promote oral health and establish good oral hygiene habits in asthmatic children.